STUDY OF CONSUMER BUYING PROCESS BASED ON AISAS MODEL, STUDY CASE: CLOUD THINK - Syukri, Khariful; Wandebori, Harimukti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This paper investigates the complexities of the fashion industry in Bandung, Indonesia, emphasizing challenges in data collection and the potential for sustainable growth. It explores the economic impact of the sector on Indonesia, detailing its significant contribution to GDP and the rise of e-commerce. The study scrutinizes the resilience of the industry during the COVID-19 pandemic, highlighting the pivotal role of trust in social media marketing. Using the AISAS consumer decision-making model, the research focuses on local fashion business Cloud Think, revealing the interconnectedness between early stages (Attention and Interest) and downstream consumer actions (Action and Share). The analysis considers demographic factors, construct reliability, and discriminant validity, providing nuanced insights into consumer behavior. The study extends to the online retail landscape, discussing pandemic effects, ethical considerations, and sustainability. In conclusion, this research offers a comprehensive understanding of the Bandung fashion industry, contributing valuable insights for businesses and policymakers navigating the evolving dynamics of the Indonesian fashion sector.